An additive manufacturing approach based on electrohydrodynamic printing to fabricate P3HT:PCBM thin films - Zulfikre Esa (19457344) (2023)
Additive manufacturing (AM) enables the production of high value and high performance components with applications from aerospace to biomedical fields. We report here on the fabrication of poly(3-hexylthiophene): phenyl-C61-butyric acid methyl ester (P3HT:PCBM) thin films through the electrohydrodynamic atomization (EHDA) process and its integration as absorber layer for organic solar cells. Prior to the film fabrication, the optimization of the process was carried out by developing the operating envelope for the P3HT:PCBM ink to determine the optimal flow rate and the appropriate applied voltage to achieve a stable-cone deposition mode. The EHDA printed thin-film’s topography, morphology and optical properties were systematically analyzed. The root-mean-square roughness was found to vary significantly with the annealing temperature and the flow rate and ranged from 1.938 to 3.345 nm. The estimated film mass and thickness were found between 3.235 and 23.471 mg and 597.5 nm to 1.60 µm, respectively. The films exhibited a broad visible absorption spectrum ranging from ~ 340 to ~ 600 nm, with a maximum peak λmax located at ~ 500 nm. As the annealing temperature and the flow rate were increased, discernible alterations in the PCBM clusters were consequently observed in the blends of the film and the size of the PCBM clusters has decreased by 3% while the distance between them was highly reduced by as much as 82%. Other Information Published in: Scientific Reports License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1038/s41598-023-43113-x